Incidental Finding of Subacute DeBakey Type II Aortic Dissection with Circular Intimal Tear in a Patient with Severe Aortic Insufficiency During the COVID-19 Pandemic - Barış Akça; Melih Doğan; Nevzat Erdil (Ukrainian Journal of Cardiovascular Surgery, 2024)
We present a case of severe aortic insufficiency diagnosed in the pandemic period with the surgery being postponed due to hygiene concerns and suspicion of COVID-19. One month later the patient’s complaints worsened. Renewed preoperative examinations revealed no difference and no sign of dissection. The suspicion of COVID-19 was eliminated, so immediate aortic valve surgery was performed despite the pandemic. Surprisingly subacute DeBakey type II aortic dissection with complete circular intimal tear came across intraoperatively. Thus, the modified Cabrol procedure was performed successfully. The diagnosis of aortic dissection may be missed, and this rate may increase in natural disasters such as pandemics and earthquakes.